An empirical study of workers’ knowledge, attitudes, and practices (KAP) regarding safety risk across demographic factors and active BBS organizations: a factorial MANOVA approach - Ali Mohammad Saedi; Zaidi Isa; Siti Sarah Salleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Construction is a high-risk sector, and construction workers engage in several activities that may expose them to grave risks. The conduct and qualities of workers may influence their awareness of workplace health and safety. Consequently, the purpose of this study was to investigate the knowledge, attitude, and practise (KAP) of employees regarding occupational safety in relation to individual characteristics and the interaction of the BBS programme at Malaysian construction sites. The one-way and two-way tests of multivariate analysis of variance were performed. Findings showed significant disparities in mean KAP scores across employee characteristics in relation to safety issues. Furthermore, the relationship between the BBS programme and personal characteristics was important in terms of employee safety attitudes and practises at the analysed construction sites. Enhancing safety (KAP) reduces employees’ divergent perceptions of workplace health and safety while simultaneously enhancing safety behaviour.